2022
DOI: 10.5098/hmt.18.37
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fin Shape on Thermal Performance Enhancement of PCM-Based Low-Grade Heat Harnessing Exchanger

Abstract: The phase change material (PCM)-based low-grade heat harnessing exchanger is used to study the recovering wasted energy from grey water. This experimental study investigated the effect of fin shape on improving the thermal performance of a PCM-based low-grade heat harnessing exchanger. Three heat exchangers of equal dimensions, namely, finless, inclined finned and V-shaped finned heat exchangers, were manufactured and tested in a container containing the PCM. A finless heat exchanger was adopted as a base case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This cooling system was especially suitable for small or medium-sized battery modules. Layth et al (2022) studied the influence of fin shape on heat transfer efficiency when PCM melted. The results showed that the heat transfer efficiency of the V-shaped fin increased by 149.88% when PCM melted.…”
Section: Introductionmentioning
confidence: 99%
“…This cooling system was especially suitable for small or medium-sized battery modules. Layth et al (2022) studied the influence of fin shape on heat transfer efficiency when PCM melted. The results showed that the heat transfer efficiency of the V-shaped fin increased by 149.88% when PCM melted.…”
Section: Introductionmentioning
confidence: 99%
“…Communications inHeat and Mass Transfer (Elsevier) Kordana-Obuch and Starzec[23] Analysis of the possibility of increasing the efficiency of the horizontal shower heat exchanger by installing baffles Energies (MDPI) Piotrowska and Słyś[21] Analysis of the efficiency of the HE in the form of linear drainage with a wavy middle wall Journal of Building Engineering (Elsevier) Jaleel and Jaffal[88] Experimental assessment of the influence of the shape of the fins on the efficiency of the phase change material-based HEFrontiers in Heat and Mass Transfer (Global Digital Central) Schestak et al[25] Presentation of a calculator supporting decision-making in the field of heat recovery from drain water in commercial kitchens, considering financial and environmental criteria Water (MDPI)Ravichandran et al[75] …”
mentioning
confidence: 99%